2017
DOI: 10.2495/ha-v2-n1-128-137
|View full text |Cite
|
Sign up to set email alerts
|

Material properties of heritage wrought steel structure based on tests

Abstract: Many heritage structures do not fulfil requirements of present standards. Decisions about adequate construction interventions should be based on complex assessment of structural reliability. Such an assessment should take into account new utility plans, actual material properties and environmental influences, including degradation processes, satisfactory past performance and advanced modelling reflecting properties of historic materials that are often distinctly different from those assumed for current constru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…He also reviewed the role of acupuncture in urology clinical practice, as well as its potential mechanisms of action and outcomes [ 2 ]. Jung K found that the actual condition and remaining service life prediction of existing TCM materials should be standardized according to the technical data obtained by monitoring [ 3 ]. Yen H R found that there is a lack of large-scale surveys of complementary TCM use in pediatric cancer patients today, with the aim of investigating the use of TCM in pediatric cancer patients.…”
Section: Related Workmentioning
confidence: 99%
“…He also reviewed the role of acupuncture in urology clinical practice, as well as its potential mechanisms of action and outcomes [ 2 ]. Jung K found that the actual condition and remaining service life prediction of existing TCM materials should be standardized according to the technical data obtained by monitoring [ 3 ]. Yen H R found that there is a lack of large-scale surveys of complementary TCM use in pediatric cancer patients today, with the aim of investigating the use of TCM in pediatric cancer patients.…”
Section: Related Workmentioning
confidence: 99%
“…This evidence thus clearly suggests that the material can be classified as wrought steel. To support this conclusion, metallurgical analysis and chemical composition investigation were carried out and confirmed that the analysed material of the girder is wrought steel [12]. Material strength based on NDTs exceeds the strength based on a tensile test by about 50%, which is common for historic steels [13].…”
Section: Input Data and Basic Assumptionsmentioning
confidence: 74%
“…Annex D of EN 1990 [6] allows estimating a design value directly from one test -such estimates are by about 10% lower than those given in Equation (7) as was shown by the previous study [12]. However, EN 1990 [6] generally recommends estimating a design value on the basis on the ratio of a characteristic value and partial factor and thus the values given in Equation (7) are further compared with the results of a fully probabilistic reliability analysis (Section 6).…”
Section: Partial Factors and Design Valuesmentioning
confidence: 85%
“…Fifteen per cent is thus the expected gain when the characteristic value of steel yield strength is estimated based on five DTs instead of a large number of NDTs. While similar observations are expected to apply for wrought irons [10], the use of tensile and compressive tests (DTs) is recommended for cast iron structures due to the inherent variability of their strength, the weaker relationship between the hardness of surface layers and tensile or compressive strength, and the overly conservative estimates of cast iron properties provided in normative documents [11,12].…”
Section: Invasiveness Of Structural Surveysmentioning
confidence: 97%